Relatively Early and Late-Onset Neuromyelitis Optica Spectrum Disorder in Central China: Clinical Characteristics and Prognostic Features - Yu, Jinbei; Yan, Shuai; Niu, Pengpeng; Teng, Junfang (Frontiers in Neurology, 2022)
Background: We aimed to analyze the clinical characteristics and prognostic features of Chinese patients with relatively late-onset neuromyelitis optica spectrum disorder (RLO-NMOSD＞40 years of age at disease onset), compared with patients with relatively early onset NMOSD (REO-NMOSD, ≤ 40 years of age at disease onset). Methods: We retrospectively reviewed the medical records of patients with NMOSD in central China (with disease courses longer than three years) between January 2012 and January 2021. We further analyzed clinical and prognostic differences between REO-NMOSD and RLO-NMOSD patients. Results: A total of 71 patients were included in this study. 39 (54.9%) of the patients had RLO-NMOSD. RLO-NMOSD patients had higher expanded disability status scale (EDSS) scores than REO-NMOSD patients at the initial (5.0 vs. 3.0, P=0.01), three-month (4.0 vs. 2.5, P=0.001), one-year (4.0 vs. 2.5, P=0.003), third-year (3.5 vs. 3.0, P=0.0017) and final follow-up (4.0 vs. 2.5, P=0.002) time points. EDSS scores of visual function were 2.0 (1.0-3.0) in REO-NMOSD and 3.0 (2.0-3.0) in RLO-NMOSD (P=0.038) at the final follow-up time point. The locations of spinal cord lesions at transverse myelitis (TM) onset were prone to cervical cord in REO-NMOSD patients There were no between-group treatment differences. The risk of requiring a cane to walk (EDSS score of 6.0) increased as the age of disease onset increased: for every 10-year increase in age of disease onset, the risk of needing a cane to walk increased by 65% (hazard ratio [HR] =1.65, 95%CI 1.15–2.38, P=0.007). Another significant predictor identified in the multivariate analysis was annualized relapse rate (ARR) (HR=2.01, 95%CI 1.09–3.71, P=0.025). We also observed a positive correlation between age at onset and EDSS scores at the final follow-up (Spearman r= 0.426, P< 0.0001) time point. EDSS scores at different periods were significantly different between RLO-NMOSD and REO-NMOSD patients with anti-aquaporin-4 (AQP4) IgG positive. Conclusion: RLO-NMOSD patients developed more severe disabilities than REO-NMOSD patients at a variety of time periods. All of the patients may experience recurrent aggravated symptoms after their first year, with only REO-NMOSD patients partly recovering from the third year. Age at onset and ARR were the main predictors of outcomes.